Post Partum Hemorrhage; Risk Factors and Management among Women Presenting to a THQ Hospital (Medical Forum Monthly, 2024)
Objective: To evaluate risk factors of post partum hemorrhage and its management among women presenting to a tertiary care hospital.Study Design: Retrospective / cross sectional studyPlace and Duration of Study: This study was conducted at the THQ hospital, Indus Hospital (Manawan Campus) Lahore from January to July 2018.Materials and Methods: Women presenting to the study hospital with post partum hemorrhage or developed it after admission during study period were included in this study. Retrospective data was collected regarding mode of delivery, causes of hemorrhage, treatment modalities and maternal mortality rate. Blood loss during post partum hemorrhage was estimated on the basis of visual parameters, history and signs of anemia in patients. Proper consent was taken from all patients included in this study and also from the ethical committee. All relevant data was properly documented and analyzed using Microsoft office and SPSS. Results: Total 900 cases were admitted in the ward for obstetrical emergency. Out of them 2.2% cases developed post partum hemorrhage. Ages of these cases were 15 to 37 years with mean age of 25 years. Out of 20 cases having PPH, 85% were severe anemic and blood transfusion was done in them, 30% cases were critical and admitted in HDU for intensive care. One patient died despite all measures, so mortality rate was 5%. Out of 20 cases 15% were delivered in other private hospitals, 25% delivered at home and 60% delivered in the study hospital. 35% mothers underwent spontaneous vaginal delivery, in 45% cases cesarean section done and in 20% cases instrumental delivery performed.Conclusion: Although post partum hemorrhage has low prevalence but it can lead to lethal complications and can be fatal. Early diagnosis and prompt management is mainstay of treatment. It can be prevented if risk factors are evaluated during pregnancy such as high parity, uterine atony, previous history of PPH or bleeding disorders, multiple pregnancies or large fetus etc.